The Exercise of Power in Strategy Meetings: A Comparison of Political Behavior in Online and Offline Meetings - Ventana Rebecca Pünchera (Junior Management Science (JUMS), 2021)
Understanding how power is exercised in strategy meetings is a vital step toward increasing the effectiveness of strategic undertakings. The objective of this master thesis is to gain important insights into issues of power and politics by investigating strategists' micropolitical tactics in online and offline meetings. Existing research has examined the exercise of power in meetings, yet there is little understanding to date regarding the evolution of political behavior in online meetings. Hence, conducting a qualitative case study, this research aims to uncover and compare the applied political tactics in online and offline meetings. Specifically, several problem-centered interviews were conducted and analyzed by means of a grounded theory approach. Furthermore, by integrating different power theories, a theoretical framework was developed. The empirical study reveals that different contextual factors impact power dimensions in meetings. Furthermore, it indicates that employees draw on specific power resources depending on whether meetings are conducted online or offline. Finally, by highlighting a paradigm shift of the exercise of power with the trend from offline to online meetings, particular attention is paid to consequences for strategic work. With these findings, the thesis contributes to the existing strategy-as-practice literature. Moreover, the generated insights provide managers with knowledge regarding the psychology of the political function of online and offline meetings.
Keywords: 650; Meeting; power; politics; political behaviour; strategy theory; strategic work